Development of a multifunctional graphene/Fe-loaded polyester textile: robust electrical and catalytic properties. Issue 47 (17th November 2020) - Morshed, Mohammad Neaz; Asadi Miankafshe, Milad; Persson, Nils-Krister; Behary, Nemeshwaree; Nierstrasz, Vincent A.
Abstract : A graphene/Fe loaded polyester fabric (PET) with robust electrical and catalytic properties has been successfully developed for the first time via a simple coating-incorporation method using hyperbranched poly(amidoamine) (PAMAM) dendrimer as the binder. Abstract : A graphene/Fe loaded polyester fabric (PET) with robust electrical and catalytic properties has been successfully developed for the first time via a simple coating-incorporation method using hyperbranched poly(amidoamine) (PAMAM) dendrimer as the binder. Both graphene oxide (GO/rGO) and zerovalent iron (Fe 0 ) nanoparticles were loaded on the polyester fabric surface before and after chemical grafting of PAMAM. Full characterization of fabrics before and after modifications has been performed by sessile droplet goniometry, ζ-potential, K/S coating evenness, SEM, XPS, FTIR, TGA and DSC analyses. The results showed successful and uniform coating of GO/rGO and loading of Fe 0 on PET and also showed the correlation between the type of chemical moiety responsible for uniform GO coating, high Fe 0 loading and their electrical and catalytic activities. Sheet resistance ( R sh ) analysis was carried out to measure the conductivity of the samples. The lowest R sh (corresponding to high conductivity) was found in PET-PAM-rGO-Fe 0 (0.74 ± 0.13 kΩ sq −1 ) followed by PET-rGO-Fe 0 (1.32 ± 0.18 kΩ sq −1 ), PET-PAM-rGO (2.96 ± 0.08 kΩ sq −1 ) and PET-rGO (3.41 ± 0.34 kΩ sq −1 ). Furthermore, Fe 0 -loaded samples were found to be effective in the catalytic removal of toxic water pollutants (crystal violet dye) with ∼99% removal of pollutants in around one hour, as observed by UV-vis spectroscopy. The relatively high electrical conductivity and catalytic activity of PET-PAM-rGO-Fe 0 are related to the role played by PAMAM in the uniform rGO coating and high Fe 0 loading. These findings are of great importance as they allow envisaging the development of multifunctional textiles for combined smart and green chemistry application.